Exploratory Factor Analysis Perilaku Belajar Generasi Z dalam Ruang Kuliah Berbasis Studio - Septian, Nandang; Firmansyah, Ahmad Yoga; Patricia, Dewa Ayu Dalia (Waca Cipta Ruang, 2024)
Classrooms significantly affect student performance and learning behavior. A substantial number of classrooms were constructed reflecting the preferences of the preceding baby boomer generation. Thus, these outdated facilities may not align with the current needs and wants of Generation Z students. Recognizing this incongruity, there is a pressing need to enhance classrooms facility. This study aims to comprehensively examine the learning behavior of Generation Z students, serving as the foundational step in the development of advanced classrooms. The investigation specifically focuses on studio-based classrooms, incorporating students with a background in design major. The primary research question pertains to the factors influencing the learning behavior of Generation Z design students in studio-based settings. Employing a quantitative approach, the research utilizes exploratory factor analysis (EFA) techniques to identify key factors influencing the learning behavior. Comprising 104 students as respondents selected through convenience sampling, were involved in the study out of a total population of 132. Data analysis conducted by using JASP statistical software, employing the EFA method, revealed three prominent factors: facility & social support, self skill, and self impetus. Keywords: learning behavior, design students, Generation Z, studio-based classrooms, EFA.